2020
DOI: 10.3390/biom10020187
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Expression Profiles in Plasma from Patients with Heart Failure Related to Platelet Activity

Abstract: Heart failure (HF) is a deadly disease that is difficult to accurately diagnose. Circular RNAs (circRNAs) are a novel class of noncoding RNAs that might play important roles in many cardiovascular diseases. However, their role in HF remains unclear. CircRNA microarrays were performed on plasma samples obtained from three patients with HF and three healthy controls. The profiling results were validated by quantitative reverse transcription polymerase chain reaction. The diagnostic value of circRNAs for HF was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…In fact, RNA-Seq has yielded many circRNAs and contributed to the discovery of the intrinsic characteristics of circRNAs [ 14 , 29 , 44 , 72 , 73 ]. More importantly, disease-relevant circRNAs can be detected in human peripheral whole blood by RNA-Seq [ 74 , 75 ].…”
Section: Technologies Available To Analyze Circrnas As Biomarkersmentioning
confidence: 99%
“…In fact, RNA-Seq has yielded many circRNAs and contributed to the discovery of the intrinsic characteristics of circRNAs [ 14 , 29 , 44 , 72 , 73 ]. More importantly, disease-relevant circRNAs can be detected in human peripheral whole blood by RNA-Seq [ 74 , 75 ].…”
Section: Technologies Available To Analyze Circrnas As Biomarkersmentioning
confidence: 99%
“…All results indicated that hsa_circRNA_025016 might be a promising biomarker for the prediction of new-onset AF after isolated off-pump CABG ( Zhang J. et al, 2018 ). Sun et al (2020) performed circRNA microarrays and found significantly upregulated plasma levels of hsa_circ_0112085, hsa_circ_0062960, hsa_circ_0053919 and hsa_circ_0014010 in HF patients. ROC analysis revealed that hsa_circ_0062960 had great potential to be a diagnostic biomarker of HF ( Sun et al, 2020 ).…”
Section: Circrnas As Biomarkers For Cvdmentioning
confidence: 99%
“… Sun et al (2020) performed circRNA microarrays and found significantly upregulated plasma levels of hsa_circ_0112085, hsa_circ_0062960, hsa_circ_0053919 and hsa_circ_0014010 in HF patients. ROC analysis revealed that hsa_circ_0062960 had great potential to be a diagnostic biomarker of HF ( Sun et al, 2020 ). A study using whole blood revealed that the hsa_circ_0037911 level was significantly increased in hypertensive patients in contrast to the control group ( Bao et al, 2018 ).…”
Section: Circrnas As Biomarkers For Cvdmentioning
confidence: 99%
“…of circRNAs Upregulated circRNAs and Originating Host Gene Upstream Gene/Regulatory Pathway Downstream Gene/Regulatory athway Ref. Ventricular septal defect embryonic heart tissue 3,072 3,162 69 Myocardial ischemia/reperfusion injury 119 66 70 Heart failure 219 447 71 dilated cardiomyopathy induced 74 Atrial fibrillation (heart tissue) 199 537 73 Atrial fibrillation (left atrial appendages) 104 374 hsa_circ_0003965 from TMEM245 glucagon signaling pathway 74 Atrial fibrillation (right atrial appendages) 268 267 hsa_circ_0004270, hsa_circ_0000075, hsa_circ_0030254, hsa_circ_0007271, etc focal adhesion pathway 74 Atrial fibrillation (both right and left appendages) 3 20 hsa_circ_0004270, hsa_circ_0000075, hsa_circ_0030254, and others ECM receptor pathway 74 hsa_circ_0000075, hsa_circ_0082096, and others SMURF1, TGFB2, GDF7, ROCK1, IFNG, LTBP1, LEFTY2, BMP6, FMOD, and FBN1 genes, TGF-β signaling pathway 74 Atrial fibrillation (atrial tissue) 57 51 circRNA-miRNA network, further GO, KEGG analysis 75 Coronary heart disease 37 73 …”
Section: Main Textmentioning
confidence: 99%
“…Another study reported 447 upregulated and 219 downregulated circRNAs in HF patients. 71 Werfel et al 72 sequenced rat, mouse, and human rRNA-depleted heart circRNA samples after treatment with RNase R. More than 9,000 circRNA candidates were detected, of which about 30% were conserved between mice and rats, and 10% were conserved among all three species. They found 40 back splices stemming from the titin (Ttn) genes, and several Ttn-derived circRNAs were specifically and strongly enriched in adult or neonatal rat hearts.…”
Section: Identification Of Circrna In Cvdmentioning
confidence: 99%